Помогите решить , вроде как с заменой переменой.Не упростить , а решить.1)[latex]sinx-cos ^{2} x=sin ^{2} x[/latex]2)[latex]6sin ^{2} x+sinx-1=0[/latex]3)[latex]cos ^{2} x-4sinx+3=0[/latex]4)[latex] \sqrt{3} sin^{2}x-3sinx*cosx...

Помогите решить , вроде как с заменой переменой.Не упростить , а решить. 1)[latex]sinx-cos ^{2} x=sin ^{2} x[/latex] 2)[latex]6sin ^{2} x+sinx-1=0[/latex] 3)[latex]cos ^{2} x-4sinx+3=0[/latex] 4)[latex] \sqrt{3} sin^{2}x-3sinx*cosx=0[/latex] 5)[latex]2sin^{2}x-\sqrt{3}sin2x=0[/latex]
Гость
Ответ(ы) на вопрос:
Гость
1) sinx - (1 - sin^2(x)) - sin^2(x) = 0 sinx - 1 + sin^2(x) - sin^2(x) = 0 sinx = 1 x = 2πk, k∈Z 2) sinx = t ∈[-1;1] 6t^2 + t - 1 = 0, D=1+4*6 = 25 t1 = (-1-5)/12 = -6/12 = -1/2, sinx = -0.5, x = π/6 + 2πk и x = 5π/6 + 2πk, k∈Z t2 = (-1+5)/12 = 4/12 = 1/3, sinx = 1/3, x = arcsin(1/3) + 2πk и x = π - arcsin(1/3) + 2πk, k∈Z 3) 1 - sin^2(x) - 4sinx + 3 = 0 -sin^2(x) - 4sinx + 4 = 0 sin^2(x) + 4sinx - 4 = 0 sinx = t ∈[-1;1] t^2 + 4t - 4 = 0, D=16+16=32 t1 = (-4-√32)/2 < -1 t2 = (-4+√32)/2, x = arcsin((-4+√32)/2) + 2πk и x = π - arcsin((-4+√32)/2) + 2πk 4) sinx*(√3*sinx - 3cosx) = 0 sinx = 0, x = πk tgx = √3, x = π/3 + πk 5) 2sin^2(x) - √3*2sinx*cosx = 0 2sinx*(sinx - √3*cosx) = 0 sinx = 0, x = πk tgx = √3, x = π/3 + πk
Не нашли ответ?
Ответить на вопрос
Похожие вопросы